(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Sewage sludgebio solids are by-products of municipal and industrial waste water treatment and a rich source of organic nutrients. Despite being an important biological resource for sustainable agriculture it is used in brick production which can be considered as an economic and environmentally sound option. This paper presents the results of the utilization of dried sludge and fly ash as brick making materials. As sludge is generated every year from STP in a large quantities in our nation, most Common method adopted for disposing the sludge is land filling. Landfill disposal of the sludge has drawbacks like high cost of transportation, difficulty in getting suitable sites for land filling, heavy metal contamination of the land, emission of foul gases etc. Thus the disposal of sludge has become a major issue in our nation. The maximum percentages of dried sludge that can be mixed with fly ash for brick making are 40 and 50 respectively.